2005
DOI: 10.1038/sj.onc.1208507
|View full text |Cite
|
Sign up to set email alerts
|

IL-2- and STAT5-regulated cytokine gene expression in cells expressing the Tax protein of HTLV-1

Abstract: Interleukin-2 (IL-2) mediates cell cycle progression and antiapoptosis in human T cells via several signal transduction pathways. The Tax protein of the human T-cell leukemia virus type I (HTLV-1) deregulates cell growth and alters the role of IL-2 in infected cells. However, Tax-immortalized cells stay dependent on IL-2, suggesting that events besides HTLV-1 gene expression are required for leukemia to develop. Here, IL-2-dependent and -independent events were analysed in a human T cell line immortalized by T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Thus, these experiments indicated that IL-2 treatment delayed the kinetics of inactivation in NK cells when treated with the antibodies to CD16 and CD94 surface receptors. Indeed, the role of IL-2 in prevention of apoptotic cell death is clearly shown in T cells (16,18,19). However, in NK cells, it is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these experiments indicated that IL-2 treatment delayed the kinetics of inactivation in NK cells when treated with the antibodies to CD16 and CD94 surface receptors. Indeed, the role of IL-2 in prevention of apoptotic cell death is clearly shown in T cells (16,18,19). However, in NK cells, it is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our observation, Fung et al and Kajiyama et al showed that IL-2 induced IL-9 production in HTLV-1-infected cell lines and allergen-specific human helper T-cell clones. 35,36 Further analysis of the IL-9 promoter would be helpful to identify transcriptional elements and epigenetic events that are responsible for IL-2-induced IL-9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…HuT-102 and MT-2), this pathway may be functionally redundant since its disruption with AG-490 failed to inhibit cellular proliferation (Kirken et al, 2000). It is of interest that many genes upregulated in HTLV-transformed cells including cyclin D2 and several cytokines are IL-2 target genes and contain Stat5 binding sites in their promoters (Fung et al, 2005).…”
Section: Cytokine Receptor Signals Including Jak/statmentioning
confidence: 99%
“…The cycD2 expression is also upregulated by IL-2 receptor signals and in part accounts for the T-cell proliferation stimulated by IL-2. The IL-2 receptor induces cycD2 by activating transcription factor Stat5, which binds directly to a cognate site in the cyclin D2 promoter (Martino et al, 2001;Moon et al, 2004;Fung et al, 2005). Tax may cooperate with IL-2-signaling either indirectly through stimulating the expression of IL2Ra or directly by activating the cycD2 promoter (Huang et al, 1997;Santiago et al, 1999).…”
Section: Cyclin D Binding and Upregulationmentioning
confidence: 99%